A plethora of isomerization processes and hydrogen scrambling in the fragmentation of the methanol dimer cation: a PEPICO study. Issue 3 (5th January 2022) - Wu, Xiangkun; Zhou, Xiaoguo; Bjelić, Saša; Hemberger, Patrick; Sztáray, Bálint; Bodi, Andras
Abstract : Photoelectron photoion coincidence reveals two new dissociative ionization channels in the methanol dimer, including C–C bond formation, and establishes the H-scrambling mechanism by partial deuteration. Abstract : The valence photoionization of light and deuterated methanol dimers was studied by imaging photoelectron photoion coincidence spectroscopy in the 10.00–10.35 eV photon energy range. Methanol clusters were generated in a rich methanol beam in nitrogen after expansion into vacuum. They generally photoionize dissociatively to protonated methanol cluster cations, (CH3 OH) n H + . However, the stable dimer parent ion (CH3 OH)2 + is readily detected below the dissociation threshold to yield the dominant CH3 OH2 + fragment ion. In addition to protonated methanol, we could also detect the water- and methyl-loss fragment ions of the methanol dimer cation for the first time. These newly revealed fragmentation channels are slow and cannot compete with protonated methanol cation formation at higher internal energies. In fact, the water- and methyl-loss fragment ions appear together and disappear at a ca. 150 meV higher energy in the breakdown diagram. Experiments with selectively deuterated methanol samples showed H scrambling involving two hydroxyl and one methyl hydrogens prior to protonated methanol formation. These insights guided the potential energy surface exploration to rationalize the dissociative photoionization mechanism. The potential energy surface was further validated by a statistical model including isotope effects to fit the experiment for the light and the perdeuterated methanol dimers simultaneously. The (CH3 OH)2 + parent ion dissociates via five parallel channels at low internal energies. The loss of both CH2 OH and CH3 O neutral fragments leads to protonated methanol. However, the latter, direct dissociation channel is energetically forbidden at low energies. Instead, an isomerization transition state is followed by proton transfer from a methyl group, which leads to the CH3 (H)OH + ⋯CH2 OH ion, the precursor to the CH2 OH-, H2 O-, and CH3 -loss fragments after further isomerization steps, in part by a roaming mechanism. Water loss yields the ethanol cation, and two paths are proposed to account for m/z 49 fragment ions after CH3 loss. The roaming pathways are quickly outcompeted by hydrogen bond breaking to yield CH3 OH2 +, which explains the dominance of the protonated methanol fragment ion in the mass spectrum.